PENGARUH TARIF PAJAK, MEKANISME MEMBAYAR PAJAK, DAN KESADARAN MEMBAYAR PAJAK TERHADAP KEPATUHAN WAJIB PAJAK UMKM - Asri Nur Hasanah; Wiwit Irawari (Jurnal Trial Balance, 2023)
This study discusses the Influence of Tax Rates, Mechanisms for Paying Taxes, and Awareness of Paying Taxes on MSME Taxpayer Compliance at the Serpong Pratama Tax Service Office. This study aims to examine the influence of tax rates, tax paying mechanisms, and awareness of paying taxes on MSME taxpayer compliance. This type of research is quantitative research. The population in this research is South Tangerang City MSME taxpayers, consisting of 3,568 taxpayers. The sample size was taken using the Slovin formula (10%) and a sample of 100 taxpayers was obtained. The data analysis technique is multiple linear regression analysis using SPSS V20. The research results show that tax rates, mechanisms for paying taxes, and awareness of paying taxes simultaneously have a positive effect on taxpayer compliance. Partially, tax rates and awareness of paying taxes have an influence and the mechanism for paying taxes has a negative influence on taxpayer compliance.